Acupuncture and moxibustion as adjunctive therapy for postoperative gastrointestinal dysfunction in gastric cancer: a systematic review and network meta-analysis - Ou, Yangxu; Lin, Dezhi; Ni, Xixiu; Feng, Chengzhi; Rong, Jing; Gao, Xiaoyu; Yu, Yang; Liu, Xinrui; Zhang, Zhiyang; Xiao, Wang; Tang, Zili; Zhao, Ling (Frontiers in Medicine, 2024)
Our study evaluated and compared the relative efficacy and safety of various adjuvant acupuncture and moxibustion techniques in treating postoperative gastrointestinal dysfunction (PGD) in gastric cancer, utilizing a network meta-analysis of 28 randomized controlled trials. Importantly, our findings indicated that routine care (RC) combined with acupuncture, acupressure, auricular acupuncture and acupoint injection were significantly more effective than RC alone. The acupuncture and moxibustion treatments showing the best therapeutic effects for PGD in gastric cancer were RC combined with acupuncture, with moxibustion and acupoint injection, and with acupressure. To the best of our knowledge, our study is the most extensive systematic review and meta-analysis on this topic, offering compelling evidence for the efficacy of acupuncture and moxibustion in PGD treatment for gastric cancer.We believe our paper will captivate your journal's readership due to the global interest in complementary and traditional medicine. Our results suggest that acupuncture and moxibustion, as adjuvant therapies, are effective and relatively safe for treating PGD in gastric cancer.